Evaluation of the project for strengthening the Profil Pelajar Pancasila - Mutiara Eka Betari; Rusman Rusman (Inovasi Kurikulum, 2024)
Basic education plays a crucial role in forming students' character and competencies. The Merdeka Curriculum in Elementary Schools carries out the Proyek Penguatan Profil Pelajar Pancasila (P5) to instill Pancasila values and develop students into lifelong learners with character. Evaluation of the achievement of P5 is essential to ensure its effectiveness and identify areas for improvement. This research aims to evaluate the achievement of P5 in Elementary Schools using the CIPP Model. This research uses a descriptive evaluation method with data collected through interviews, observation, document study and questionnaires. The results of the context evaluation show that the curriculum at SDPN 252 Setiabudi, Bandung City follows the principles of Kurikulum Merdeka, providing freedom in adapting learning and integrating Pancasila values. Input evaluation shows that facilities are adequate, but several deficiencies need to be corrected. Teachers need additional training to understand the development of project modules. Process evaluation shows that the implementation of P5 is going well, but there are obstacles related to the lack of timeliness and coordination of the Expo-Project, requiring better planning. Product evaluation shows that P5 has succeeded in developing positive student behavior and awareness of Pancasila values.   Abstrak Pendidikan dasar berperan krusial dalam membentuk karakter dan kompetensi peserta didik. Kurikulum Merdeka di Sekolah Dasar mengusung Proyek Penguatan Profil Pelajar Pancasila (P5) untuk menanamkan nilai-nilai Pancasila dan mengembangkan peserta didik menjadi pembelajar sepanjang hayat yang berkarakter. Evaluasi ketercapaian P5 menjadi esensial untuk memastikan efektivitasnya dan mengidentifikasi area perbaikan. Tujuan penelitian ini adalah mengevaluasi ketercapaian P5 di Sekolah Dasar menggunakan Model CIPP. Penelitian ini menggunakan metode evaluasi deskriptif dengan data yang dikumpulkan melalui wawancara, observasi, studi dokumen, dan angket. Hasil evaluasi konteks menunjukkan kurikulum di SDPN 252 Setiabudi Kota Bandung sesuai dengan prinsip Kurikulum Merdeka, memberikan kebebasan dalam adaptasi pembelajaran dan integrasi nilai-nilai Pancasila. Evaluasi input menunjukkan fasilitas memadai, namun beberapa kekurangan perlu diperbaiki. Guru membutuhkan pelatihan tambahan untuk memahami pengembangan modul proyek. Evaluasi proses menunjukkan pelaksanaan P5 berjalan baik, tetapi ada hambatan terkait ketidaktepatan waktu dan koordinasi Expo-Project, memerlukan perencanaan yang lebih baik. Evaluasi produk menunjukkan P5 berhasil mengembangkan perilaku positif peserta didik dan kesadaran akan nilai-nilai Pancasila. Kata Kunci: CIPP; evaluasi proyek pembelajaran; P5; sekolah dasar